Validation of the Asthma Illness Representation Scale (AIRS©) - Sidora-Arcoleo, Kimberly (J Asthma, 2010)
BACKGROUND: Research has suggested a link between parents' illness representations (IRs), use of complementary and alternative medicine, inhaled/oral corticosteroids and leukotriene antagonists, and children's health outcomes. The Asthma Illness Representation Scale (AIRS©) provides a structured assessment of the key components of asthma IRs allowing the healthcare provider (HCP) to quickly identify areas of discordance with the professional model of asthma management. METHODS: These analyses extend the initial validation of the AIRS© and compares data from the original study conducted among a primarily white and African American sample in Rochester, NY (N = 228) with data obtained from a predominantly inner-city, ethnic minority sample (Puerto Rican, African American, and Afro-Caribbean) from the Bronx, New York (N = 109). RESULTS: A larger proportion of the Rochester sample was white and non-poor and had graduated high school. Bronx parents were more likely to perceive their child's asthma to be moderate or severe than the Rochester parents. Bronx children were older and had longer duration of asthma and reported more acute health care visits (past year). Bronx parents reported total AIRS© scores more closely aligned with the lay model than Rochester parents. The AIRS© instrument demonstrated acceptable internal reliability among the Bronx sample (total score α = 0.82) and the AIRS© subscale Cronbach's alpha coefficients were remarkably similar to those obtained from the original validation study (range = 0.54–0.83). Poor parents and those with less than a high school education had lower total AIRS© scores than their counterparts. White parents had AIRS© scores more closely aligned with the professional model compared to each of the ethnic subgroups. A perception of less severe asthma, fewer reports of asthma and somatization symptoms, and a positive HCP relationship were associated with IRs congruent with the professional model. IRs aligned with the professional model were associated with fewer acute asthma-related healthcare visits. CONCLUSIONS: The AIRS© instrument exhibited good internal reliability, external validity, and differentiated parents based on ethnicity, poverty, and education. Assessment of asthma IRs during the healthcare visit will allow the HCP and parent to discuss and negotiate a shared asthma management plan for the child, which will hopefully lead to improved medication adherence and asthma health outcomes.